Optimasi Produksi untuk Meminimasi Total Biaya pada Usaha Mikro Kecil Menengah - Adisti Rosmasari; Wandhansari Sekar Jatiningrum (Jurnal Rekayasa Sistem Industri, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of Indonesian economy. Therefore, it is considered important to notice the condition of MSMEs in Indonesia. The business process in MSMEs usually conducted traditionally, included in determining total amount of production. As a result, sometimes there is a buildup of inventory which causes an increase in the total production cost. On the other hand, lost sales can also occur due to the amount of production couldn’t meet demand. This study aimed to solve production optimization problem with the objective function of minimizing total costs by considering inventory. It is expected that consumer demand can always be fulfilled and there is no overstock through optimization. A case study was conducted in Al-Barik MSME in Bantul Regency which produces various of snacks. Its strategic location makes Al-Barik MSME visited by tourists frequently to buy souvenirs, such as chips. This research was conducted using linear programming with LINGO. According to optimal solution, the minimum total cost spent on banana chips, bitter melon chips, and chili chips for a month was Rp. 98.227.900. Total inventory cost also decreased by an average 82.8% for each product during a month. The optimization made MSME’s able to meet the demand for each product at each period. Therefore, the profit obtained from the three types of products increased by Rp. 3.061.925 in a month.